The Race with No Finish Line Assessing the Strategy of Regional Great Power Competition - Skold, Martin (Marine Corps University Press (MCUP), 2023)
The Race with No Finish Line offers a framework for understanding the strategies of states engaged in competition for regional hegemony. Employing insights drawn from business strategy, the author argues for an essentially asymmetric understanding of fundamental policy goals for states engaged in competition for control of a region of the globe, with one state attempting to maintain a dominant position and another attempting, by focusing limited resources, to supplant it.